Problems and service needs among ex-offenders with HIV risk behaviors entering sober living recovery homes - Polcin, Douglas L. (Criminal justice studies, 2017)
There is currently a nationwide effort to decrease the number of persons who are incarcerated in jails and prisons. However, many ex-offenders on probation or parole do not have access to affordable housing and larger proportions have histories of HIV risk as well as substance abuse problems. In California, sober living houses (SLHs) are becoming an increasingly popular housing option for these individuals. Based largely on the principles of alcoholics anonymous, SLHs require abstinence from alcohol and drugs and provide peer support for recovery. The current study examined the types of problems experienced among 330 ex-offenders with lifetime risk for HIV during the six months prior to entering SLHs. Nearly three fourths (74%) of all ex-offenders entering the houses had at least one HIV risk. The importance of housing was evident in the finding that housing status and participants’ perceptions of their housing situation were associated with a variety of problem areas, including substance use, HIV risk, psychiatric severity, and legal problems. SLHs represent an important housing option for ex-offenders, but many residents may need additional services to address various problems.